Isoquinolinequinone Derivatives from a Marine Sponge (Haliclona sp.) Regulate Inflammation in In Vitro System of Intestine - Kim, Yun Na (Mar Drugs, 2021)
Using bio-guided fractionation and based on the inhibitory activities of nitric oxide (NO) and prostaglandin E2 (PGE2), eight isoquinolinequinone derivatives (1–8) were isolated from the marine sponge Haliclona sp. Among these, methyl O-demethylrenierate (1) is a noble ester, whereas compounds 2 and 3 are new O-demethyl derivatives of known isoquinolinequinones. Compound 8 was assigned as a new 21-dehydroxyrenieramycin F. Anti-inflammatory activities of the isolated compounds were tested in a co-culture system of human epithelial Caco-2 and THP-1 macrophages. The isolated derivatives showed variable activities. O-demethyl renierone (5) showed the highest activity, while 3 and 7 showed moderate activities. These bioactive isoquinolinequinones inhibited lipopolysaccharide and interferon gamma-induced production of NO and PGE2. Expression of inducible nitric oxide synthase, cyclooxygenase-2, and the phosphorylation of MAPKs were down-regulated in response to the inhibition of NF-κB nuclear translocation. In addition, nuclear translocation was markedly promoted with a subsequent increase in the expression of HO-1. Structure-activity relationship studies showed that the hydroxyl group in 3 and 5, and the N-formyl group in 7 may be key functional groups responsible for their anti-inflammatory activities. These findings suggest the potential use of Haliclona sp. and its metabolites as pharmaceuticals treating inflammation-related diseases including inflammatory bowel disease.